URBAN TRANSFORMATION IN RAJASTHAN: AN EVALUATION OF AMRUT AND SMART CITIES INITIATIVES - Gandhi , Nayan Prakash; Jaiswal , Virat (LPPM Universitas Bina Bangsa, 2025)
This paper critically assesses the impact of two major urban development initiatives in Rajasthan, India: the Atal Mission for Urban Renewal and Transformation (AMRUT) and the Smart Cities Mission (SCM). Using a mixed methodology, integrating secondary data analysis and qualitative interviews with stakeholders from selected cities, the study assesses the progress, challenges, and achievements of these missions in the context of the unique urban landscape of Rajasthan. The analysis focuses on key parameters such as infrastructure development, improved service delivery, economic growth, environmental sustainability, and citizen participation. The results reveal both successes and limitations in the implementation of AMRUT and SCM, highlighting the need for context-specific strategies, better coordination among ministries, and a greater focus on inclusive and sustainable urban development to achieve meaningful urban transformation in Rajasthan.